Resposta:
resposta: S = {-5/6}
Explicação passo a passo:
Resolvendo equação exponencial:
[tex]9^{x + 1} = \sqrt[3]{3}[/tex]
[tex](3^{2} )^{x + 1} = 3^{\frac{1}{3} }[/tex]
[tex]3^{2x + 2} = 3^{\frac{1}{3} }[/tex]
[tex]2x + 2 = \frac{1}{3}[/tex]
[tex]2x = \frac{1}{3} - 2[/tex]
[tex]2x = \frac{1 - 6}{3}[/tex]
[tex]2x = \frac{-5}{3}[/tex]
[tex]x = -\frac{5}{6}[/tex]
Aprenda mais sobre equações exponenciais, acessando:
https://brainly.com.br/tarefa/47995420
https://brainly.com.br/tarefa/11731759
https://brainly.com.br/tarefa/34352254
https://brainly.com.br/tarefa/31167051
https://brainly.com.br/tarefa/1408744
https://brainly.com.br/tarefa/45935032
https://brainly.com.br/tarefa/46317830